The Association Between Inflammatory Markers and Hypertension. A Call for Anti-Inflammatory Strategies? - Néstor H. García; Luis I. Juncos (The Scientific World Journal)
The most important goal of antihypertensive therapy is to prevent the complications associated with hypertension (stroke, myocardial infarction, end-stage renal disease, etc). For this, secondary targets such as left ventricular hypertrophy, proteinuria, dementia, and other signs of hypertension-induced organ damage help the physician to assess risks and monitor treatment efficacy. New treatment targets may be arising, however. One such target may be endothelial dysfunction. In effect, endothelial dysfunction not only may precede the elevation of blood pressure, but may also pave the way to conditions often associated with hypertension, such as diabetes, arteriosclerosis, microalbuminuria, congestive heart failure, and tissue hypertrophy. Because inflammation often accompanies endothelial dysfunction, approaches to counteract inflammation are now being evaluated. For this, antagonists of the renin-angiotensin-aldosterone system, statins, and beta blockers are all being tested. All of these agents seem to prevent or delay the induction of proinflammatory molecules aside from, and in addition to, their specific effects on blood pressure. The focus of this review is to update some of the animal and human research showing that hypertension sets off an inflammatory state and also to consider some of the anti-inflammatory approaches that may prevent the development of endothelial dysfunction, and the subsequent renal and cardiovascular damage.